Bio-Insecticidal Nanoemulsions of Essential Oil and Lipid-Soluble Fractions of Pogostemon cablin - Manjesh, Keerthiraj; Kundu, Aditi; Dutta, Anirban; Saha, Supradip; Neelakanthaiah, Bhagyasree Sira (Frontiers in Plant Science, 2022)
The present study aimed to develop nanoemulsions (NEs) of essential oil (EO) and lipid-soluble extract (HE) of Pogostemon cablin leaves using biosurfactant, saponin. Hydro-distilled EO and fat soluble HE were analysed using GC-MS revealed 38.7±2.7% and 37.5±2.1% patchoulol, respectively. to profile volatile aromatic constituents. EO and HE were formulated with saponin to prepare corresponding coarse emulsions (CEs), further high-speed homogenization for 2 min followed by ultrasonification for 3 min with constant frequency of 50 kHz. of the CEs resulted respective NEs. Critical Micelle Concentration (CMC) of saponin has been determined to finalize its concentration to prepare the NEs. NEs were characterized for physico-chemical properties such as, emulsion intrinsic stability, particle size distribution, polydispersity index (PDI), Transmission Electron Microscopy (TEM) for morphology and accurate nanodroplet diameters. CEs and NEs were investigated for insecticidal efficacy against female adults of Tetranychus urticae and larvae of Spodoptera litura. GC-MS analysis of EO and HE revealed 38.7±2.7 and 37.5±2.1% of the most abundant patchouli alcohol, respectively. Stable NEs of EO and HE at 500 µg mL-1 concentration exhibited corresponding average particle size of 51.7 and 89.9 nm, while, TEM image revealed spherical shaped droplets with the average droplet diameters of 15.3 and 29.4 nm, respectively. EO and HE of P. cablin thus, nano-emulsified with saponin were found more stable and cause appreciably higher insecticidal potential even at the sub lethal concentrations. NEs of EO and HE displayed highest efficacy in contact toxicity (LC50 43.2 and 58.4 µg mL-1) after 48 h and fumigant toxicity (LC50 9.3 and 13.6 µg mL-1) after 24 h against T. urticae, respectively. Additionally, NEs of EO showed considerable antifeedant and feeding deterrent action (AI 99.21±0.74 and FI 99.73±1.24) against S. litura larvae. Developed efficient, green NEs of EO and lipid-soluble fractions of P. cablin could be evaluated further under in vivo multilocation trials for the development of bio-insecticide.